2022
DOI: 10.1002/adma.202110278
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Multi‐Bit Nonvolatile Memory Based on a van der Waals Heterostructure with a 2D‐Perovskite Floating Gate

Abstract: inevitable, which reduces the reliability in high-density integration. Furthermore, uncontrollable interface is detrimental to the retention time and operation speed of the memory device. 2D van der Waals (vdW) crystals manifest ultra-thin layered structure, highly anisotropic in-and outof-plane conductivity and superior carrier migration, [6] which are promising to solve the above problems. Over the past decade, 2D vdW atomic crystals, such as graphene, MoS 2 , ReS 2 , etc., are widely used as the composed el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…2D Ruddlesden-Popper perovskite (2D-RPP) materials with unique inorganic/organic alternating chain structure have received attention recently in non-volatile floating gate memory. [19,20] Due to the insulating nature of the long organic chain, it is possible that the organic chain layer itself functions as an insulating tunneling layer as that in FG structure, while the trapping ability of charge are determined by the chain length and the multiple defect states in the inorganic layer. [21] Besides, 2D-RPP are photosensitive materials that provide tunable band structures via component engineering, which is essential in interface band alignment design and broadband photoelectric application.…”
Section: Introductionmentioning
confidence: 99%
“…2D Ruddlesden-Popper perovskite (2D-RPP) materials with unique inorganic/organic alternating chain structure have received attention recently in non-volatile floating gate memory. [19,20] Due to the insulating nature of the long organic chain, it is possible that the organic chain layer itself functions as an insulating tunneling layer as that in FG structure, while the trapping ability of charge are determined by the chain length and the multiple defect states in the inorganic layer. [21] Besides, 2D-RPP are photosensitive materials that provide tunable band structures via component engineering, which is essential in interface band alignment design and broadband photoelectric application.…”
Section: Introductionmentioning
confidence: 99%
“…When the laser pulses are irradiated on the device, considerable photogenerated electron/hole pairs will be induced in the semiconducting channel, which is shown in Figure S12g. Since holes are easier to tunnel through the h-BN insulating layer than electrons, more holes tunnel into the floating gate layer to recombine with the stored electrons, resulting in a reduced net charge in the floating gate layer . With the number of optical pulses increasing, optical-induced multilevel switching states can be obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Photogenerated electrons (holes) in the channel unable to recombine with carriers of opposite polarity and accumulate in the channel, resulting in persistent EPSC does not disappear but maintains for a period of time instead of immediate disappearance. [94][95][96][97][98][99] Tran et al [89] reported a floating gate field effect transistor based on MoS 2 /h-BN/graphene heterostructure (Figure 8a). The fabricated optical memory device could control electron tunneling to the graphene floating gate layer to modulate the resistance of the MoS 2 channel and realize the programmable function of optical memory by using the source-drain voltage and light illumination.…”
Section: Floating Gate Transistorsmentioning
confidence: 99%